Underestimated Sink of Atmospheric Mercury in a Deglaciated Forest Chronosequence - Wang Xun; Yuan Wei; Lin Che-Jen; Luo Ji; Wang Feiyue; Feng Xinbin; Fu Xuewu; Liu Chen (Environmental Science & Technology, 2020)
Mercury (Hg) deposition through litterfall has been regarded as the main input of gaseous elemental mercury (Hg-0) into forest ecosystems. We hypothesize that earlier studies largely underestimated this sink because the contribution of Hg-0 uptake by moss and the downward transport to wood and throughfall is overlooked. To test the hypothesis, we investigated the Hg fluxes contributed via litterfall and throughfall, Hg pool sizes in moss covers and woody biomass as well as their isotopic signatures in a glacier-to-forest succession ecosystem of the Southeast Tibetan Plateau. Results show that Hg-0 depositional uptake and pool sizes stored in moss and woody biomass increase rapidly with the time after glacier retreat. Using the flux data as input to a Hg isotopic mixing model, Hg deposition through litterfall accounts for 27-85% of the total accumulation rate of Hg-0 in organic soils of glacial retreat over 20-90 years, revealing the presence of additional sources of Hg-0 input. Atmospheric Hg-0 accounts for 76 +/- 24% in ground moss, 86 +/- 15% in tree moss, 62-92% in above ground woody biomass (branch-bark-stem), and 44-83% in roots. The downward decreasing gradient of atmospheric Hg-0 fractions from the above ground woody biomass to roots suggests a foliage-to-root Hg transport in vegetation after uptake. Additionally, 34-82% of atmospheric Hg-0 in throughfall further amplifies the accumulation of He from atmospheric sources. We conclude that woody biomass, moss, and throughfall represent important Hg-0 sinks in forest ecosystems. These previously unaccounted for sink terms significantly increase the previously estimated atmospheric Hg-0 sink via litterfall.